Endovascular Repair of Popliteal Artery Pseudoaneurysm With Arteriovenous Fistula After Knee Arthroscopy: Case Report and Literature Review. (February 2014) - Alserr, Ayman H. K.; Antonopoulos, Constantine N.; Papapetrou, Anastasios; Kakisis, John D.; Brountzos, Elias; Liapis, Christos D.
We report a case of postarthroscopic popliteal artery pseudoaneurysm (PSA) with arteriovenous fistula (AVF; PSA-AVF) in a 53-year-old woman who presented with limb edema, pain, and bruit 1 year after arthroscopic meniscectomy. She was treated percutaneously by covered stent deployment. After 6 months of follow-up, the patient was asymptomatic, with patency of the stent and occlusion of the AVF. A review of the literature was also performed to investigate the prevalence of postarthroscopic PSAs and highlight the endovascular approach of treatment. Endovascular approach with covered stent appears to be less invasive and might be an effective and feasible way of treatment of postarthroscopic popliteal PSA-AVF.